Kas nauja apie Žygimanto Augusto bibliotekos paveldą Sankt Peterburge - Braziūnienė, Alma (Senoji Lietuvos literatūra, 2018)
Catalogue of books from the Library of Sigismund II Augustus, King of Poland in the collection of the National Library of Russia in Saint Petersburg = Katalog książek z biblioteki króla Zygmunta II Augusta w zbiorach Rosyjskiej Biblioteki Narodowej w Sankt Petersburgu = Каталог книг из библиотеки короля Сигизмунда Августа в фондах Российской национальной библиотеки в Санкт-Петербурге, National Library of Poland, Warsaw, National Library of Russia, Saint Petersburg, edited by Maria I. Tkachenko, Maria Brynda, Warsaw: Biblioteka Narodowa, 2015, 198 p., [21] iliustr. p.: iliustr., lent., faks. ISBN 978-83-7009-621-2